Hubungan Asupan Kalium, Asupan Kalsium Dan Rasio Lingkar Pinggal Pinggul Dengan Tekanan Darah Pada Pasien Hipertensi Wanita Menopause Rawat Jalan Di Rsud Sukoharjo - Mutumanikam, Ratri; , Ririn Yuliati S.Si.T., M.Si (2016)
Introduction:The risk of hypertension in women increases after experiencing menopause due to a decrease in estrogen and progesterone hormones results in a decrease in endothelial cells the elasticity function that can affect blood pressure. The prevalence of hypertension in Sukoharjo general hospital as much as 9.4% and increased by 84% over the last 3 years between the years 2012-2014. Objective:To determine the relationship of potassium intake, calcium intake and waist to hip ratio to the blood pressure among hypertensive menopausal women at Sukoharjo general hospital. Research methods: This research is observational study with cross sectional design. Total subjects of 30 menopausal hypertensive were selected through systemic consequtive sampling. potassium intake and calcium intake obtained through semiquantitative food frequency. The waist to hip ratio obtained by methlin while the blood pressure was obtained from hospital medical records. Results:90.0% of the subjects has low potassium intake while 26.7% of the subject has enough calcium intake. A total of 60% of the subjects were abnormal waist to hip ratio, and 60% of the subjects had hypertension type II. The results show that potassium intake is associated with systolic blood pressure (p=0,001) and diastolic blood pressure (p=0,027). Calcium intake has a relationship with systolic and diastolic blood pressure with p=0,026, and p=0,018 respectively. Waist to hip ratio also has a relationship with systolic and diastolic blood pressure with p=0,002 and p=0,023respectively. Conclusion:There is a relationship of blood pressure to potassium intake, calcium intake and waist to hip ratio.